Caterpillar cereal as a potential complementary feeding product for infants and young children: nutritional content and acceptability. Issue 4 (December 2015) - Bauserman, Melissa; Lokangaka, Adrien; Kodondi, Kule‐Koto; Gado, Justin; Viera, Anthony J.; Bentley, Margaret E.; Engmann, Cyril; Tshefu, Antoinette; Bose, Carl
Abstract: Micronutrient deficiency is an important cause of growth stunting. To avoid micronutrient deficiency, the World Health Organization recommends complementary feeding with animal‐source foods. However, animal‐source foods are not readily available in many parts of the Democratic Republic of Congo (DRC). In such areas, caterpillars are a staple in adult diets and may be suitable for complementary feeding for infants and young children. We developed a cereal made from dried caterpillars and other locally available ingredients (ground corn, palm oil, sugar and salt), measured its macro‐ and micronutrient contents and evaluated for microbiologic contamination. Maternal and infant acceptability was evaluated among 20 mothers and their 8–10‐month‐old infants. Mothers were instructed in the preparation of the cereal and asked to evaluate the cereal in five domains using a Likert scale. Mothers fed their infants a 30‐g portion daily for 1 week. Infant acceptability was based on cereal consumption and the occurrence of adverse events. The caterpillar cereal contained 132 kcal, 6.9‐g protein, 3.8‐mg iron and 3.8‐mg zinc per 30 g and was free from microbiologic contamination. Mothers' median ratings for cereal characteristics were (5 = like very much): overall impression = 4, taste = 5, smell = 4, texture = 4, colour = 5, and consistency = 4. All infants consumed more than 75% of the daily portions, with five infants consuming 100%. No serious adverse events were reported. We conclude that a cereal made from locally available caterpillars has appropriate macro‐ and micronutrient contents for complementary feeding, and is acceptable to mothers and infants in the DRC.